SUBCLINICAL HYPOTHYROSIS IN WOMEN OF FERTILE AGE - Oybutaeva N. U.; Negmatova G. Sh. (Web of Journals Publishing, 2024)
Excess iodine is known to affect thyroid function, and in predisposed individuals even a moderately increased iodine intake may cause hypothyreosis or hyperthyreosis. In our material, one patient developed hypothyreosis and five patients hyperthyreosis after using commercial health products containing iodine.
Keywords: menstrual irregularities, fertile age, pregnancy, subclinical hypothyroidism.